Flora of Borneo : The vascular plant genera - Wong, Sin Yeng (Firenze University Press, 2023)
A checklist of all genera of ferns and fern allies, gymnosperms, and angiosperms that are found in Borneo is presented. The native, introduced, and endemic status for all taxa is given. This checklist comprises 271 families: 39 families (ferns and fern allies), 5 families (gymnosperms), and 227 families (angiosperms) of 1877 genera and 12590 species. There are 1592 native genera, 192 introduced genera, 73 endemic genera, and 20 genera with both native and introduced species present.